A Randomized Controlled Trial of Chinese Medicine on Nonmotor Symptoms in Parkinson's Disease. (23rd May 2017) - Chua, Ka-Kit; Wong, Adrian; Chan, Kam-Wa; Lau, Yin-Kei; Bian, Zhao-Xiang; Lu, Jia-Hong; Liu, Liang-Feng; Chen, Lei-Lei; Chan, Ka-Ho; Tse, Kim-Pong; Chan, Anne; Song, Ju-Xian; et al.
Abstract : Nonmotor symptoms (NMS) of Parkinson's disease (PD) have devastating impacts on both patients and their caregivers. Jiawei-Liujunzi Tang (JLT) has been used to treat some NMS of PD based on the Chinese medicine theory since Qing dynasty. Here we report a double-blind, randomized, placebo-controlled, add-on clinical trial aiming at evaluating the efficacy and safety of the JLT in treating NMS in PD patients. We randomly assigned 111 patients with idiopathic PD to receive either JLT or placebo for 32 weeks. Outcome measures were baseline to week 32 changes in Movement Disorder Society-Sponsored Revision of Unified PD Rating Scale (MDS-UPDRS) Parts I–IV and in NMS assessment scale for PD (NMSS). We observed improvements in the NMSS total score (p = 0.019 ), mood/cognition (p = 0.005 ), and reduction in hallucinations (p = 0.024 ). In addition, post hoc analysis showed a significant reduction in constipation (p < 0.001 ). However, there was no evidence of improvement in MDS-UPDRS Part I total score (p = 0.216 ) at week 32. Adverse events (AEs) were mild and comparable between the two groups. In conclusion, long-term administration of JLT is well tolerated and shows significant benefits in improving NMS including mood, cognition, and constipation.